The effect of interval training exercises on the development of performance endurance and some physiological variables among young soccer players (Journal of Humanities and Social Sciences Research, 2023)
The aim of the research is to identify the effect of exercises by the method of interval training in developing performance endurance and some physiological variables among young soccer players the research sample consisted of Al-medhatia football club players , and the researcher used the experimental approach by designing the two groups with a pre and post test a sample of Al-medhatia football club players for the season (2022-2023) consisted of (20) players who were chosen randomly ,the researcher conducted the full research procedures , and after extracting the results , which were treated using the appropriate statistical methods , the conclusion were reached , the most important of which are :Interval training exercises have a positive effect on the development of performance endurance of some physiological variables (heartbeat number-BOP –LDH-LA ) for young soccer players , in the light of the conclusions of the researcher , the researcher recommended that trained attention should be the development of the phenomena and the performance of the players to keep abreast of modern football requirements.